A Comparative Clinical Study To Evaluate The Efficacy Of Kasisa Churna And Puga Churna Avachurnana In Vrana - Rao A, Babitha; vardhana, Harsha (International Research Journal of Ayurveda & Yoga, 2021)
Healthy healing of Vrana is most important part of surgery it can be Nija (endogenous) and Agantu – (exogenous) or Shastrakrit; it’s not merely deals with good closure of wound but also maintain its anatomical and functional integrity with minimal scar formation without complications . Avachurnana used in superficial/ Deep and foul-smelling ulcers covered with layers of deranged fat. Shodhana (purification) and Ropana (healing) being safer, easy, potent and economic procedure useful to establish even Vaikrutapaham (to restore normalcy to scar). Kasisa is Shothahara (anti inflammatory), Rujahara, (analgesic) Krumihara (wormicidal) , Sankochakaraka etc, ingredient in Vrana Chikitsa kalpa’s - vrana Ropana churna, Vrana Shodhana Sutra/Varti, Roma Sanjana yoga etc. Patient belongs to whichever geographical area, the medicine grown in same region is hita; Puga, locally cultivated, available worldwide, economic, ingredient in various vrana yoga’s - Ghontaphaladi Varti; Pugadi yoga, Pugadi lepa, mocha-Pugadi ksheera etc; it possesses Kashaya rasa which aids vrana Ropana; Kledahara, Malahara, Rusha – Sankochakaraka, Shotahara, raktasthambana etc. Brinraja Bhavita Kasisa Churna and Puga Churna avachurnana (Topical Medicated Dusting) in Randomized comparative clinical study with Group A overall result is 94.21% and Group B overall result is 91.10% which shows statically significant results in both groups. Comparative analysis of the overall effect of the treatments in both the groups with unpaired t-test shows that the treatment is not significant in Group A. No Incidences of complications like infection, aggravation of Lakshana, recurrence or any other adverse effects were found during the study